Prevalence of Major Depressive Disorder in Survivors of Sexual assault Examined in a Medical College of West Bengal - Ghosh, I; Chowdhury , S; Biswas , S (Journal of Indian Academy of Forensic Medicine, 2024)
Rape is a heinous crime committed against women which has an impact on physical health as well as mental health. Post-traumatic stress disorder and major depressive disorders are commonly encountered by the survivors. This study tries to overview this and find out the prevalence of major depressive disorder in survivors of sexual assault. In general, developing countries are in dearth of data regarding this and the objectives of this study were to find the prevalence of major depressive disorder in adult and adolescent survivors of sexual assault. The study was based on a pre-validated Public Health Questionnaire and scoring was done accordingly. The instruments used were PHQ-9 and PHQ-A in English, Bengali and Hindi. The sample size of the study was 41, out of which 5 refused to give consent. Out of the 36 survivors, 21 (58.33%) were adults and 15 (41.66%) were adolescents. The legal cut-off of 18 years, as prevalent in India was used to classify the study population between adolescents and adults. In 15 adults and 12 adolescents, the perpetrator was known. In 6 adults and 3 adolescent the perpetrator was unknown. Multiple incidences of offence were committed in 24 (66.66%) subjects. Tentative diagnosis of depression was made in 15 (71.4%) adults and 6 (40%) adolescents. In adults, 40% suffered from mild form of major depression. In adolescents, 50% had minimal symptoms and 50% suffered from severe form of major depression. From the study, it can be concluded that Major Depressive Disorder is very much prevalent in the survivors of sexual assault. Interventional, longitudinal studies are required in this field for the proper follow-up and assessment of the survivors.